Wilfrid Almendra - light boiled like liquid soap - Almendra, Wilfrid 1972-; McIntosh, Alexandra; Schafhausen, Nicolaus 1965- (Sternberg Press, 2019)
Light Boiled like Liquid Soap' is an immersive installation by Marseille-based artist Wilfrid Almendra featuring radio transmissions and a series of sculptural elements made of copper, plaster, and silicone in various states of dematerialization. Combining found and repurposed materials, the works attest to notions of desire, circulation, and flux, from protective spaces of retreat to global economies of exchange. The seventh volume in the 'Fogo Island Arts' publication series accompanies the eponymous exhibition curated by Alexandra McIntosh and Nicolaus Schafhausen and presented at the Fogo Island Art Gallery in 2016. Richly illustrated with color photographs of Almendra's installation, the book features a critical essay by Anne Faucheret, a work of speculative fiction by Nicolas Idier, poetry by Jorge Armando Sousa, and a conversation between Wilfrid Almendra, Alexandra McIntosh, and Nicolaus Schafhausen. Exhibition: Fogo Island Galery, Canada (25.03. - 09.10.2016)
Colophon: This catalogue is published on the occasion of the exhibition "Wilfrid Almendra - Light Boiled Like Liquid Soap", Fogo Island Gallery, March 25 to October 9, 2016
Keywords: Almendra, Wilfrid -- 1972-; Almendra, Wilfrid / Exhibitions; Installations (Art) / Exhibitions; Almendra, Wilfrid / Expositions; Installations (Art); Exhibition catalogs; Ausstellungskatalog -- Fogo Island Arts -- 25.03.2016-09.10.2016 -- Fogo